2013
DOI: 10.1371/journal.pone.0075428
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Down Syndrome Screening on Taiwanese Down Syndrome Births: A Nationwide Retrospective Study and a Screening Result from a Single Medical Centre

Abstract: A retrospective analysis of the Taiwanese National Birth Defect Registration and Notification System was conducted in order to determine the live birth- and stillbirth rates in infants with Down syndrome, trisomy 18, trisomy 13 and Turner syndrome between 2001 and 2010. The objective was to investigate the impact of Down syndrome screening on the Taiwanese Down syndrome live birth rate. In addition, the results of first-trimester Down syndrome screening between 2006 and 2011, and of second-trimester quadruple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…44 In Taiwan, a termination rate of 67.5% was reported for 2001 45 ; however, prenatal screening and diagnosis has since been more widely introduced and the live birth rate for children with DS decreased from 48.7% in 2001 to 6% in 2010. 23 Comparison between termination rates reported prior to the introduction of NIPT with termination rates seen in the reviewed studies and audits suggests a general trend towards a decrease in termination rates compared with pre-NIPT rates (Table 2). Data from the UK audit and research studies [35][36][37] indicate that termination rates for women having NIPT are considerably lower than the pre-NIPT termination rate of 92%.…”
Section: Literature Review Of Pregnancy Outcomes Following Niptmentioning
confidence: 95%
See 1 more Smart Citation
“…44 In Taiwan, a termination rate of 67.5% was reported for 2001 45 ; however, prenatal screening and diagnosis has since been more widely introduced and the live birth rate for children with DS decreased from 48.7% in 2001 to 6% in 2010. 23 Comparison between termination rates reported prior to the introduction of NIPT with termination rates seen in the reviewed studies and audits suggests a general trend towards a decrease in termination rates compared with pre-NIPT rates (Table 2). Data from the UK audit and research studies [35][36][37] indicate that termination rates for women having NIPT are considerably lower than the pre-NIPT termination rate of 92%.…”
Section: Literature Review Of Pregnancy Outcomes Following Niptmentioning
confidence: 95%
“…11,18 It is not yet clear, however, whether the increase in the numbers of women having prenatal testing will directly result in more terminations of pregnancy. There will be wide variation in the number of children born with DS between and even within countries depending on atti- These figures vary between countries: in the United States there were 30% fewer individuals with DS (2007), 19 50% fewer in the Netherlands (2015), 20 48% fewer in England and Wales (2008), 21 55% fewer in Australia (2004), 22 94% fewer in Taiwan (2010), 23 and 55% fewer in China (2011). 24 As the numbers of older women giving birth have grown, the numbers of pregnancies affected with DS have also increased.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Several studies conducted prior to the introduction of NIPT have reported the number of children born with DS compared to expected numbers based on the prevalence of DS in the general population. These figures vary between countries: in the United States there were 30% fewer individuals with DS (2007), 50% fewer in the Netherlands (2015), 48% fewer in England and Wales (2008), 55% fewer in Australia (2004), 94% fewer in Taiwan (2010), and 55% fewer in China (2011) . As the numbers of older women giving birth have grown, the numbers of pregnancies affected with DS have also increased.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005 and 2008, this program was modified to perform screening during the first or second trimester and to use a combined test for nuchal translucency thickness, hCG and pregnancy‐associated plasma protein‐A (PAPP‐A) or the quadruple test (hCG, AFP, uE3, and inhibin A) (Chou et al, , Shaw et al, , Shaw et al, ). The first and second trimester DS screening percentage is approximately 48.7% in Taiwan (Lin et al, ). According to the literature, the detection rate for the second trimester double test is 56‐61%, the first trimester combined test is 82.0–87.5%, and the second trimester quadruple test is 81% in Taiwan (Shaw et al, , Shaw et al, ).…”
Section: Changes In Down Syndrome Prevalence With Prenatal Diagnosis mentioning
confidence: 99%